Language as Custody — Writing Without Harm in Post-Interpretive Criticism - Vale, Dorian (Museum of One, 2025)
Language as Custody — Writing Without Harm in Post-Interpretive Criticism By Dorian Vale In this critical essay, Dorian Vale addresses the often overlooked violence of language in art criticism. Drawing from the philosophical core of Post-Interpretive Criticism (PIC), this work reframes writing not as interpretation, but as custody—an act of ethical stewardship over what cannot be explained without distortion. Vale explores how clinical, ironic, or overly descriptive language can flatten the moral gravity of witness-based artworks—particularly those dealing with trauma, silence, exile, or the sacred. Instead of attempting to decode or resolve these works, the essay proposes a discipline of linguistic restraint, where words become protective vessels rather than invasive instruments. Through real case studies and comparative language analysis, Language as Custody offers both a conceptual foundation and practical framework for how one might write without harm. The goal is not to say more, but to write in a way that holds what the work cannot say aloud. This is not a guide for translation—it is a doctrine for presence. A refusal to violate what resists interpretation. And in that refusal, it calls for a quieter, more reverent kind of authorship. Vale, Dorian. Language as Custody — Writing Without Harm in Post-Interpretive Criticism. Museum of One, 2025. DOI: 10.5281/zenodo.17077653 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) post-interpretive criticism, Dorian Vale, study guide for art criticism, five principles of art ethics, ethical witnessing in art, presence over interpretation, restraint in criticism, moral proximity, viewer as evidence, rejecting performance, contemporary art criticism, poetic criticism, art education resources, museum pedagogy, witnessing trauma in art, art writing without interpretation, anti-interpretation philosophy, critique without harm, non-extractive art writing
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://osf.io/xa5jw/ https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://osf.io/zhnre/ https://doi.org/10.5281/zenodo.17069115 https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 http://eprints.rclis.org/47186/ http://eprints.rclis.org/47182/ http://eprints.rclis.org/47197/ http://eprints.rclis.org/47210/  http://eprints.rclis.org/47209/  http://eprints.rclis.org/47208/ http://eprints.rclis.org/47207/  http://eprints.rclis.org/47206/ http://eprints.rclis.org/47203/ http://eprints.rclis.org/47187/ http://eprints.rclis.org/47201/ http://eprints.rclis.org/47204/ http://eprints.rclis.org/47202/ http://eprints.rclis.org/47199/ http://eprints.rclis.org/47198/ http://eprints.rclis.org/47196/  http://eprints.rclis.org/47191/ http://eprints.rclis.org/47193/ http://eprints.rclis.org/47194/ http://eprints.rclis.org/47195/ http://eprints.rclis.org/47192/ https://core.ac.uk/works/299793749/?t=ccf14485c84f6196dcddf51a8410bc88-299793749 https://core.ac.uk/works/299795319/?t=ccf14485c84f6196dcddf51a8410bc88-299795319 https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale&page=1 https://core.ac.uk/works/299792897/?t=ccf14485c84f6196dcddf51a8410bc88-299792897 https://core.ac.uk/works/299793648/?t=ccf14485c84f6196dcddf51a8410bc88-299793648 https://core.ac.uk/works/299793082/?t=ccf14485c84f6196dcddf51a8410bc88-299793082 https://core.ac.uk/works/299793838/?t=ccf14485c84f6196dcddf51a8410bc88-299793838 https://core.ac.uk/works/299794146/?t=ccf14485c84f6196dcddf51a8410bc88-299794146 https://core.ac.uk/works/299793310/?t=ccf14485c84f6196dcddf51a8410bc88-299793310 https://core.ac.uk/works/299793166/?t=ccf14485c84f6196dcddf51a8410bc88-299793166 https://africarxiv.ubuntunet.net/handle/1/10438 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 https://africarxiv.ubuntunet.net/handle/1/10465 https://africarxiv.ubuntunet.net/handle/1/10466 https://africarxiv.ubuntunet.net/handle/1/10467 https://africarxiv.ubuntunet.net/handle/1/10468 https://africarxiv.ubuntunet.net/handle/1/10469 https://africarxiv.ubuntunet.net/handle/1/10470 https://africarxiv.ubuntunet.net/handle/1/10471 https://africarxiv.ubuntunet.net/handle/1/10472 https://africarxiv.ubuntunet.net/handle/1/10473 https://africarxiv.ubuntunet.net/handle/1/10474 https://africarxiv.ubuntunet.net/handle/1/10475 https://africarxiv.ubuntunet.net/handle/1/10476 https://africarxiv.ubuntunet.net/handle/1/10477 https://africarxiv.ubuntunet.net/handle/1/10478 https://africarxiv.ubuntunet.net/handle/1/10479 https://africarxiv.ubuntunet.net/handle/1/10480 https://africarxiv.ubuntunet.net/handle/1/10481 https://africarxiv.ubuntunet.net/handle/1/10482 https://africarxiv.ubuntunet.net/handle/1/10483 https://africarxiv.ubuntunet.net/handle/1/10484 https://africarxiv.ubuntunet.net/handle/1/10485 ISBN: 978-1-0698203-0-3 ISBN: 978-1-0698203-1-0 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen.
Keywords: Ontology of beauty; Independent Philosopher of Art; Criticism and Reception Theory; Founder of Post-Interpretive Criticism; The Viewer as Evidence; Alternative art criticism; Aesthetics; Post-Interpretive Criticism; Language as Custody; Language as violence; Divine proximity in aesthetics; Radical art restraint; Restraint in front of art; Witness Aesthetics; Museum of One; Art Criticism Ethics; Witness over interpretation; Interpretive silence; Quiet philosophy of art; Philosophy of Art; Custodianship of Art; Ethics in Art Criticism; Visual Culture Studies; Ethical art theory; Interpretation and Meaning; Post-Interpretive Lexicon; Epistemology of witness; Art Theory; Erasure as Afterlife; Aesthetic mercy; Moral proximity; Stillmark Theory; Art as Truth; Criticism beyond interpretation; Post-Aesthetic Critic; Erasure as ethics; Custodian of Witness Aesthetics; Art as Presence; Art Writer and Theorist; Dorian Vale; Silence as method; New art criticism movement; nterpretation vs. Witnessing; Art encounter ethics; Contemporary Aesthetics; Phenomenology and Art